Renal Lymphangiectasia: A Diagnostic and Therapeutic Challenge - L, Mourabiti; Y, Allata; G, El Bardai; BA, Chouhani; N, Kabbali; T, Sqalli Houssaini; Y, Bouabdallah; K, Khattala; O, Alaoui; M, Boubou; M, Hida; FZ, Souilmi (Journal of Clinical Nephrology, 2024)
Renal lymphangiectasia, a rare lymphatic disorder, manifests as cystic infiltration in the perirenal and para-pyelic space due to lymphatic drainage defects. Diagnosis hinges on imaging modalities like ultrasound, CT, and MRI. However, lack of awareness can lead to confusion with other renal cystic pathologies. Here, we present a case of renal lymphangiectasia in a child, detailing diagnostic and therapeutic strategies. The patient, a 2-year-old and 2-month-old girl from a consanguineous marriage, presented with persistent abdominal distension. Clinical examination revealed growth retardation and normal blood pressure but abdominal distension with dullness. Lab investigations indicated acute renal failure with non-nephrotic proteinuria. Radiologically, renal lymphangiectasia was confirmed by ultrasound showing microcysts and perirenal cystic lesions with ascites, corroborated by MRI and CT scans. Treatment involved nephroprotective therapy and diuretics for ascites. Surgical intervention was necessitated due to cyst size and compressive nature, involving iterative punctures, marsupialization, and percutaneous drainage. Postoperatively, recurrent ascites temporarily worsened renal function but returned to baseline afterward. renal lymphangiectasia necessitates careful management due to its potential to progress to chronic renal failure. The prognosis depends on factors like initial proteinuria severity, treatment response, and complication management. Personalized approaches are pivotal in its diagnosis and management.